2019
DOI: 10.1016/j.lungcan.2018.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive clinicopathological features of adenocarcinoma in situ and minimally invasive adenocarcinoma of the lung: A retrospective study

Abstract: The aim of this study was to investigate distinguishing clinicopathological features, in addition to histological invasiveness, in adenocarcinoma in situ (AIS) and minimally invasive adenocarcinoma (MIA) of the lung. Materials and methods: Patients with lung adenocarcinoma who underwent surgery at our hospital between 2007 and 2014 were reviewed, focusing on computed tomography (CT) images, operative procedures and clinical outcomes, histopathology, Ki-67 immunostaining, and EGFR-mutation status. EGFR mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 25 publications
5
22
0
Order By: Relevance
“…Even though many studies have demonstrated that segmentectomy can be a reasonable alternative for stage I lung adenocarcinoma, especially for those ≤2 cm, most of these studies did not investigate the impact of pathological subtypes, 6‐8 which is a significant limitation because according to the IASLC/ATS/ERS classification, lung adenocarcinoma consists of heterogeneous subtypes (AAH, AIS, MIA, and IAC) with varying biological behaviors and prognoses 13,14 . The equivalent outcomes between segmentectomy and lobectomy in prior studies may be driven by the good prognosis of AAH/AIS/MIA, for which, segmentectomy is adequate 14‐16,18,28 . However, for IACs, which are more aggressive with poorer outcomes, it is still unclear whether segmentectomy is equivalent to lobectomy in terms of oncologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though many studies have demonstrated that segmentectomy can be a reasonable alternative for stage I lung adenocarcinoma, especially for those ≤2 cm, most of these studies did not investigate the impact of pathological subtypes, 6‐8 which is a significant limitation because according to the IASLC/ATS/ERS classification, lung adenocarcinoma consists of heterogeneous subtypes (AAH, AIS, MIA, and IAC) with varying biological behaviors and prognoses 13,14 . The equivalent outcomes between segmentectomy and lobectomy in prior studies may be driven by the good prognosis of AAH/AIS/MIA, for which, segmentectomy is adequate 14‐16,18,28 . However, for IACs, which are more aggressive with poorer outcomes, it is still unclear whether segmentectomy is equivalent to lobectomy in terms of oncologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with AAH/AIS/MIA, the 5‐year postsurgical survival is nearly 100% regardless of the extent of surgical resection and thus segmentectomy is a reasonable treatment 2,15‐18 . However, for early‐stage IAC, whether segmentectomy can achieve outcomes equivalent to those of lobectomy is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…When surgically resected, they have been shown to have close to a 100% 5-year survival. 15,16 However, these preinvasive lesions can only be differentiated from benign processes once surgically resected and not from needle biopsy. 14 This limitation can result in diagnostic operations for benign lesions or no treatment for possibly precancerous lesions.…”
Section: Perspectivementioning
confidence: 99%
“…The AIS type was defined as a small (≤3 cm), localized adenocarcinoma consisting of a pure lepidic component without an invasive component. The MIA type was defined as a small (≤3 cm), solitary adenocarcinoma with a predominantly lepidic growth, and an invasive component of ≤5 mm that lacked vascular, lymph gland, alveolar, or pleural invasion (6)(7)(8)(9)(10). It has been hypothesized that morphologically, these two subtypes show a gradual malignant progression from AIS to MIA (11,12).…”
Section: Introductionmentioning
confidence: 99%